Nasal Delivery of Antioxidants by Cholesterol-incorporated Liposomes Extends the Neuroprotective Time Window in Cerebral Ischemia - Min, Seul K.; Kwon, Yeo Seon; Cho, Myung Kwon; Shin, Hwa Sung (Current Pharmaceutical Design, 2017)
Antioxidants have the potential to prevent cerebral ischemia-reperfusion (IR)-associated secondary damage induced by reactive oxygen species (ROS); however, the short therapeutic time window of IR is a considerable obstacle. Nano-sized nasal delivery systems provide an effective means of delivering drugs through the BBB, but few such systems have been developed to extend the treatment time window in IR. In this work, a nanosized nasal delivery system for antioxidants was found to have the potential to extend the neuroprotective time window. The authors chose to use the antioxidant C-phycocyanin (C-Pc) to design a neuroprotective liposome with a long life, controllable release, and high neuronal uptake rate. Liposomes formulated with various cholesterol to phospholipid ratios were assessed thermodynamically, kinetically, and biologically. Thermodynamically stable, monodispersive, and release-controllable C-Pc liposomes were more effectively taken up by Neuro2a cells than free C-Pc and were biocompatible, maintaining the anti-oxidative properties of C-Pc. When optimal C-Pc liposomes were administered to middle cerebral artery occlusion (MCAO) rats 2 h after onset, infarct sizes were smaller and behavioral activities improved compared with the same metrics in free C-Pc-treated rats. Liposomal delivery still reduced infarct sizes and improved behavioral activity 6 h after onset, whereas free C-Pc did not.
Keywords: Time window